What is behind water user satisfaction with irrigation organizations´ performance? An empirical analysis under different water scarcity conditions - Carlos Bopp; Alejandra Engler; Cristian Jordan; Roberto Jara-Rojas (Agricultural Water Management, 2024)
The level of satisfaction of individuals within a community sharing a common pool resource is essential to strengthening collective actions. In the case of irrigation water, which is becoming a critical resource due to its declining availability in many regions worldwide, the satisfaction level in Water User Associations (WUAs) is not guaranteed and also varies across individuals within these organizations. This study analyzed the satisfaction of users in WUAs and identified organization- and user-level characteristics associated with it. Using a sample of 393 users of 20 WUAs from the Mediterranean portion of Chile, we performed confirmatory factor analysis, correlational analyses, and multilevel regressions. A composite indicator of user satisfaction showed significant correlations with the positive evaluation of the WUA staff performance, the effectiveness of monitoring and enforcement, and the confidence that other users do not withdraw more water than they are allocated. We also compared users’ satisfaction levels from WUAs facing higher and lower water scarcity problems and found that user satisfaction is significantly higher in the latter case. The results of the multilevel econometric models show that in WUAs under higher water scarcity, user satisfaction is affected by several structural characteristics (water withdrawal mechanism and location along the canal) and users' human and social capital variables (experience, education, and participation in organizations); in contrast, in WUAs with a low level of scarcity, few covariates were significant while unobserved characteristics became more relevant (34 % of total variance explanation). Our study contributes to the existing literature on user satisfaction in community resource management, which could be useful to promote effective and cohesive governance structures as, ultimately, users determine cooperation rates and willingness to participate in WUA actions.